Effect of Bt traits on transgenic rice’s growth and weed competitiveness - Kang-xu WANG; Ke-rou ZHANG; Cou-gui CAO; Yang JIANG (Journal of Integrative Agriculture, 2023)
Transgene escape could lead to genetically modified rice establishing wild populations in the natural environment and competing for survival space with weeds. However, whether the expression of the Bacillus thuringiensis (Bt) gene in rice will alter the relationship between transgene plants and weeds and induce undesirable environmental consequences are poorly understood. Thus, field experiments were conducted to investigate the weed competitiveness and assess the ecological risk of transgenic Bt rice under herbicide-free and lepidopterous pest-controlled environments. Results showed that weed–rice competition in the direct-sowing (DS) field was earlier and more severe than that in the transplanting (TP) field, which resulted in a significant decrease in biomass and yield in DS. However, conventional Bt and non-Bt rice yield was not significantly different. The weed number, weed coverage ratio, and weed diversity of conventional Bt rice were significantly higher than those of non-Bt rice at the early growth and mature stages, especially in DS plots, suggesting that Bt traits did not increase the weed competitiveness of transgenic rice and had no negative effect on weed diversity. Grain yield and weed number varied between different hybrid rice lines, but those differences were insignificant between Bt and non-Bt rice. The number of insects increased with the increase of weeds in hybrid rice plots, whereas the insect number and diversity did not display a significant difference between Bt and non-Bt rice. Therefore, the ecological risk of transgenic Bt rice is comparable to non-Bt rice.